2016
DOI: 10.18632/oncotarget.8273
|View full text |Cite
|
Sign up to set email alerts
|

BCL6 modulation of acute lymphoblastic leukemia response to chemotherapy

Abstract: The bone marrow niche has a significant impact on acute lymphoblastic leukemia (ALL) cell phenotype. Of clinical relevance is the frequency with which quiescent leukemic cells, in this niche, survive treatment and contribute to relapse. This study suggests that marrow microenvironment regulation of BCL6 in ALL is one factor that may be involved in the transition between proliferative and quiescent states of ALL cells. Utilizing ALL cell lines, and primary patient tumor cells we observed that tumor cell BCL6 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Coculture Study. Coculture conditions have been previously described (Slone et al, 2016b). Briefly, 1 Â 10 6 REH or REH/Ara-C cells were seeded on either BMSC or HOB adherent layers and Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coculture Study. Coculture conditions have been previously described (Slone et al, 2016b). Briefly, 1 Â 10 6 REH or REH/Ara-C cells were seeded on either BMSC or HOB adherent layers and Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To study drug resistance in leukemic cells, we previously developed an in vitro coculture model consisting of humanderived ALL cells cultured in the presence of either primary human bone marrow stromal cells (BMSCs) or primary human osteoblasts (HOBs) (Moses et al, 2016b). Using this model, we developed a protocol to isolate and characterize a subset of phase dim (PD) leukemic cells buried under the BM-derived adherent layer (Slone et al, 2016b). PD cells share the characteristics typical of relapsed/refractory leukemic cells, in that they are quiescent and resistant to chemotherapy, have impaired microRNA biogenesis, and are relevant to the current study on manifested altered mitochondrial metabolism (Moses et al, 2016a,b;Slone et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…The leukemic cells which were buried under the BMSC were separated by size exclusion with G10 sephadex after vigorous washing to remove all leukemic cells adhered to the top of the BMSC [9]. Buried leukemic cells were designated phase dim cells (PD) and have been previously described to be the most chemotherapy-resistant population [11, 12]. As such, they are not assumed to be identical, but rather are used as a model, for refractory tumor cells that are known to be clinically problematic in the treatment of ALL.…”
Section: Methodsmentioning
confidence: 99%
“…The PD tumor cells are used to model cells that contribute to MRD in vivo based on phenotypic similarities [9]. Using this niche-based co-culture model, we have reported that primary ALL samples, or ALL cells in co-culture with the BM cellular components, have reduced BCL6 expression in the PD cell population [10]. Furthermore, reduction in BCL6 resulted in disruption of cell cycle progression, with cyclin D3-dependent accumulation of cells in the G0/G1 phase.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, reduction in BCL6 resulted in disruption of cell cycle progression, with cyclin D3-dependent accumulation of cells in the G0/G1 phase. The importance of BCL6 in maintaining cell quiescence, drug resistance and the resulting MDR phenotype was further validated in vivo by demonstrating significant event free survival in mice treated with a combination of caffeine (stabilizer of BCL6) and cyatarabine (Ara-C) when compared to mice treated with Ara-C alone [10]. BCL6 has also been shown to be a master regulator of glycolysis by directly repressing the overall gene program of the glycolytic pathway [11].…”
Section: Introductionmentioning
confidence: 99%